Preparation method of ultra-fine grain hard alloy mixture

Through a two-stage grinding process, lightweight Ti(C,N)-WC-Ni cermet cylinder and cemented carbide ball were used for grinding, which solved the composition uniformity and sintering in ultrafine crystal WC-Co carbide. The performance problem has achieved the improvement of alloy performance.

CN119410945APending Publication Date: 2025-02-11ZIGONG CEMENTED CARBIDE CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411414829.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent composition uniformity and sintering performance when preparing ultrafine crystal WC-Co carbides, resulting in abnormal growth of WC grains, thick clamping phenomenon, and reducing alloy performance.

Method used

Two-stage grinding process is adopted, the first stage uses a lightweight Ti(C,N)-WC-Ni cermet cylinder as the grinding body to reduce the impact kinetic energy and achieve efficient mixing; the second stage uses cemented carbide balls as grinding The crushing efficiency is improved and a highly dispersed ultrafine powder is obtained.

Benefits of technology

The uniform mixing of materials is achieved, processing strain and lattice distortion during grinding process is reduced, the integrity of WC grains is maintained, the performance of the alloy is improved, and the abnormal growth and thickening of WC grains are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410945A_ABST
    Figure CN119410945A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultra-fine grain hard alloy mixture, which belongs to the technical field of hard alloy manufacturing, and comprises the following steps: weighing raw material powder of WC, Co, Cr3C2, VC and the like, carrying out two-stage grinding and mixing on the raw material powder to obtain a mixture, and then pressing and sintering to obtain the ultra-fine grain WC-Co hard alloy. The two-stage grinding process is adopted, uniform mixing of materials is facilitated, machining strain and lattice distortion in the grinding process are effectively reduced, the integrity and morphology of WC grains are kept, and therefore the crushing efficiency of the materials is improved, and superfine powder with higher dispersity is obtained. According to the prepared ultra-fine grain WC-Co hard alloy, the components are evenly mixed, particle contact and reaction are more sufficient in the sintering process, abnormal growth of WC grains in the alloy can be effectively avoided, the problem of coarse inclusion is solved, and the performance of the alloy is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide manufacturing, in particular to a method for preparing an ultrafine-grained cemented carbide mixture. Background Art

[0002] Ultrafine-grained WC-Co cemented carbide is widely used in cutting tools, mining tools and wear-resistant parts due to its excellent hardness, strength and wear resistance. Ultrafine-grained WC-Co cemented carbide usually uses ultrafine WC powder as raw material, but ultrafine WC powder is easy to agglomerate due to its large specific surface area, and it is not easy to mix evenly with Co during ball milling. In addition, in order to inhibit grain growth, grain growth inhibitors are usually added, and these additives also face the problem of mixing uniformity. Therefore, when preparing ultrafine-grained WC-Co cemented carbide, how to obtain a mixed powder with appropriate particle size, uniform composition, and excellent molding and sintering properties is a technical challenge. At present, the industrial preparation of cemented carbide mixtures mainly adopts wet grinding, that is, alcohol or hexane is used as the grinding medium, and the powders of WC, Co and grain inhibitors are put into the grinder, and the grinding and mixing process is carried out using the grinding body. The shape of the grinding body can be a sphere (generally 4 to 10 mm in diameter), or it can be a cylindrical or polyhedron of comparable size. Among them, cylindrical or other shaped grinding bodies have low grinding efficiency, and the prepared mixed powder has large particle size, which is generally used for the preparation of coarse-grained or ultra-coarse-grained cemented carbide with low grinding efficiency; spheres have high grinding efficiency and uniform mixing, and are widely used to prepare ultra-fine-grained WC-Co cemented carbide mixtures. However, the traditional wet grinding process is used to prepare ultra-fine-grained WC-Co mixtures, because it takes a long grinding time to make the mixture uniform, which leads to large grinding kinetic energy, severe powder processing strain, poor formability of the mixture, and high sintering activity. During the sintering process, the grains are prone to abnormal growth, resulting in the coarsening of WC grains in the alloy, thereby reducing the performance of the alloy.

[0003] Patent CN102202817B discloses a ball milling process for cemented carbide mixtures, which is characterized by using a stirring ball milling process to improve the ball milling efficiency. In this process, the diameter of the cemented carbide balls is 4 to 6 mm, the speed of the stirring arm is 100 to 135 rpm, and the ball milling time is 6 to 8 hours. Due to the movement of the grinding balls and the limitations of the internal structure of the grinding barrel, the mixture in some areas may not be fully ground, resulting in uneven grinding of the mixture.

[0004] Patent CN103537702B discloses a method for preparing nano WC-Co alloy powder with high bending strength. The method prevents oxidation of the powder by wet grinding under argon protection under vacuum conditions, thereby improving the uniformity and dispersibility of the powder composition. At the same time, the grain growth of WC-Co cemented carbide is inhibited by adding nano rare earth oxides. Although this method can prevent powder oxidation, it fails to solve the problem of high sintering activity of the mixture caused by grinding and abnormal grain growth during sintering; at the same time, the dispersion uniformity of the added nano rare earth oxides is difficult to ensure.

[0005] Patent CN117684036A discloses an ultrafine-grained cemented carbide and its preparation method. The WC grain size distribution of the cemented carbide obtained by the optimized ball milling process is uniform, which can reduce the coarse crystal aggregation and WC grain inclusion phenomenon. The method adopts a segmented ball milling method. The first stage of ball milling time is 1 to 5 hours. First, WC powder accounting for 15 to 25% of the mass of WC powder is added with Cr3C2 powder, VC powder, alcohol accounting for 1 / 5 of the volume of alcohol, and surfactant for pre-mixing. In the second stage of ball milling, the powder milled in the first stage, Co powder, and the remaining WC powder are ball milled, and the remaining alcohol and molding agent are added. The second stage of ball milling time is 23 to 40 hours. This method adopts a two-stage wet grinding process to prepare the mixture. The entire wet grinding process uses carbide balls as grinding bodies for mixing and crushing. The total ball milling time is 24 to 45 hours. When the total ball milling time is short, it is difficult to ensure the uniformity of the mixture. When the total ball milling time is long, the kinetic energy generated during the grinding and crushing process is large, and the grains are very easy to grow during the sintering process.

[0006] Patent CN113201677A discloses a production process for producing ultrafine-grained cemented carbide from subfine tungsten carbide. By adopting a production process of multiple ball milling, multiple stops, high ball-to-material ratio, and special temperature sintering, the purpose of processing WC powder with a particle size of 0.4 to 0.6 μm, that is, subfine tungsten carbide, into ultrafine-grained cemented carbide is achieved. The total wet milling time is 48 to 150 hours, and the next ball milling is performed after staying for 4 to 5 hours after each ball milling, and the number of ball millings is 3 to 5 times. This method uses multiple segmented wet milling to ensure the uniformity of the mixture, but the total wet milling time reaches 48 to 150 hours, and cemented carbide balls are used for grinding, the grinding kinetic energy is large, and the grains are prone to abnormal growth during the sintering process.

[0007] Patent CN102994792A discloses a method for preparing high-strength and high-hardness nanocrystalline tungsten-cobalt cemented carbide, which uses sub-fine WC powder as raw material to prepare a mixture through intensive grinding + wet grinding, wherein the intensive grinding uses chemical reagent Tween 80 to improve the grinding efficiency, the grinding medium is a mixture of acetone and n-hexane, and the grinding is carried out for 24 to 48 hours using cemented carbide balls, with a ball-to-material ratio of 3.25:1; the wet grinding uses cemented carbide balls for grinding for 24 hours, with a ball-to-material ratio of 5:1. Although this method can save costs, the use of cemented carbide balls to intensively crush sub-fine WC powder for 24 to 48 hours and wet grinding of the mixed powder for 24 hours, the whole process of grinding kinetic energy is large and the duration is long, which will lead to a large sintering activity of the mixture, and the WC grains are easy to grow during the sintering process, resulting in the phenomenon of coarse inclusion.

[0008] Patent CN109457163B discloses an ultrafine-grained cemented carbide material without rare earth elements and a preparation method thereof, wherein the powder after ball milling is spray-dried to obtain a granulated mixture with a stable carbon / oxygen ratio, low impurity content, uniform spherical particle size, good fluidity, and stable flow rate. This method fails to solve the problem of high kinetic energy during the grinding process and high sintering activity of the mixture.

[0009] Patent CN103890204A discloses a non-contact mixer that uses resonant sound waves to achieve powder mixing to maintain the particle size, particle size distribution and morphology of WC particles for the preparation of high-strength and toughness cemented carbide. Although this method has a good mixing effect, it does not crush the original agglomerated WC powder, resulting in the formation of coarse grains in the agglomerated WC powder during the sintering process.

[0010] It can be seen that the methods of the prior art still have difficulty in solving the problems of uniform dispersion of ultrafine WC, Co, and inhibitors when preparing ultrafine-grained cemented carbide, as well as the abnormal growth of WC grains during sintering. Although the prior art patents provide ideas and methods for preparing ultrafine-grained cemented carbide mixtures, in actual applications, it is necessary to consider multiple factors such as cost, operational complexity, safety, and final product performance, and it is not suitable for industrial production. Therefore, providing a new ultrafine-grained WC-Co cemented carbide mixture preparation process that can obtain a mixture powder with appropriate particle size, uniform composition, and excellent molding and sintering properties is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0011] In view of this, in order to solve the shortcomings of the traditional cemented carbide mixture grinding process, the present invention adopts a two-stage grinding process to prepare an ultrafine-grained WC-Co cemented carbide mixture. The first stage of the grinding process uses a lightweight Ti(C,N)-WC-Ni metal ceramic cylinder as a grinding body, which is conducive to reducing the impact kinetic energy during grinding, achieving efficient mixing of materials, and at the same time reducing the processing strain and lattice distortion of the powder, reducing sub-grain defects, maintaining the complete morphology of WC grains, improving the quality of the mixture, and enhancing the performance of the alloy; the second stage of the grinding process uses a cemented carbide ball as a grinding body to further improve the crushing efficiency of the material, obtain highly dispersed ultrafine powder, and thus obtain high-performance ultrafine-grained WC-Co cemented carbide.

[0012] To achieve the above object, the present invention adopts the following technical solution:

[0013] A method for preparing an ultrafine-grained cemented carbide mixture comprises the following steps:

[0014] (1) Weigh WC, Co, Cr3C2 and VC powders to obtain a formula material;

[0015] (2) The formulated materials are ground and mixed in two stages, and a forming agent is added to obtain a mixed material, which is then pressed and sintered to obtain an ultrafine-grained WC-Co cemented carbide.

[0016] Furthermore, the powder raw material composed of WC, Co, Cr3C2 and VC in step (1) is composed of the following mass percentages: WC 86.9-92.7%, Co 6.5-12%, Cr3C2 0.5-0.9%, and VC 0.2-0.4%.

[0017] Furthermore, the powder particle size of the WC is less than 0.5 μm, and the powder particle size of the Co powder is about 1.0 μm.

[0018] Preferably, the WC powder particle size is 0.4 μm.

[0019] Furthermore, the molding agent is paraffin, and the amount of the molding agent used is 2.0-3.0% of the mass of the alloy raw material.

[0020] Furthermore, the operation method of the two-stage grinding in step (2) is as follows: in the first stage grinding process, a lightweight Ti(C,N)-WC-Ni metal ceramic cylinder with a specification of D3-6mm×L10-20mm is used as a grinding body, and the weight ratio of the grinding body to the formula material is 2:1-4:1;

[0021] The second grinding process uses D6-10mm carbide balls as grinding bodies, and the weight ratio of the grinding bodies to the formula materials is 4:1-8:1.

[0022] Furthermore, the grinding media used in the first stage of grinding and the second stage of grinding are both hexane;

[0023] Add 300-450 mL of grinding media per kg of formula.

[0024] Furthermore, the grinding speed of the first stage grinding is 36 to 40 r / min, and the grinding time is 12 to 36 hours.

[0025] The grinding speed of the second stage grinding is 36 r / min, and the grinding time is 6 to 18 hours.

[0026] Furthermore, the density of the lightweight Ti(C,N)-WC-Ni metal ceramic cylinder is 6.5 g / cm 3 .

[0027] Furthermore, the sintering temperature in step (2) is 1405-1445°C, and the sintering holding time is 50-70 minutes.

[0028] The beneficial effects of the present invention are as follows: the present invention adopts a two-stage grinding process, which is conducive to achieving uniform mixing of materials, effectively reducing processing strain and lattice distortion during the grinding process, and maintaining the integrity and morphology of WC grains, while improving the crushing efficiency of the material to obtain a more highly dispersed ultrafine powder. The present invention adopts a two-stage grinding process, which significantly shortens the grinding time of the material, reduces powder processing strain, and improves the formability of the mixture. The ultrafine-grained WC-Co cemented carbide prepared by the present invention has uniformly mixed components, and the particle contact and reaction during the sintering process are more sufficient, which can effectively avoid the abnormal growth of WC grains in the alloy, solve the problem of coarse inclusions, and effectively improve the performance of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a metallographic image of the ultrafine-grained WC-6.5%Co cemented carbide prepared in Example 1 of the present invention, magnified 1500 times, and its structure is uniform with few coarse grains.

[0030] Figure 2 The metallographic image of the ultrafine-grained WC-6.5%Co cemented carbide prepared in Comparative Example 2 of the present invention is magnified 1500 times, and a large number of coarse grains are present. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] WC-6.5%Co ultrafine-grained cemented carbide was prepared, and the composition by mass fraction was 92.6%WC, 6.5%Co, 0.55%Cr3C2, and 0.35%VC, wherein the powder particle size FSSS of WC was 0.4μm, and the powder particle size FSSS of Co was 1.0μm.

[0034] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0035] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 37.5 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic (density 6.5 g / cm 3 )D3mm*L20mm rods were used as grinding bodies, the weight ratio of grinding bodies to raw material powder was 2:1, the rotation speed was 36r / min, and after grinding for 24 hours, the pre-abrasive was obtained after drying and sieving.

[0036] (2) Weigh 600 g of pre-ground material and put it into a 1 L ball mill, then add 400 mL of hexane for grinding. Use D6 mm carbide balls as grinding bodies, the weight ratio of grinding body to powder material is 8:1, the rotation speed is 36 r / min, and after grinding for 6 hours, dry and sieve to obtain a mixed material.

[0037] (3) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0038] The metallographic and performance results of the sample alloy are shown in Table 1. The WC-6.5%Co ultrafine-grained cemented carbide prepared by the above two-stage grinding process has higher magnetic force and hardness and good coarseness control.

[0039] Example 2

[0040] WC-9%Co ultrafine-grained cemented carbide is prepared, and the composition is as follows: 89.9%WC, 9.0%Co, 0.85%Cr3C2, 0.25%VC by mass fraction, wherein the powder particle size FSSS of WC is 0.4μm, and the powder particle size FSSS of Co is 1.0μm.

[0041] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0042] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 45 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod was used as the grinding body. The weight ratio of the grinding body to the powder material was 2:1. The rotation speed was 36 r / min. After grinding for 24 hours, the pre-abrasive was dried and sieved to obtain the pre-abrasive.

[0043] (2) Weigh 600 g of pre-ground material and put it into a 1 L ball mill, then add 400 mL of hexane for grinding. Use D6 mm carbide balls as grinding bodies, the weight ratio of grinding body to powder material is 8:1, the rotation speed is 36 r / min, and after grinding for 6 hours, dry and sieve to obtain a mixed material.

[0044] (3) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0045] The metallographic and performance results of the sample alloy are shown in Table 1. The WC-9%Co ultrafine-grained cemented carbide prepared by the two-stage grinding process has higher magnetic force and hardness and good coarseness control.

[0046] Example 3

[0047] WC-12%Co ultrafine-grained cemented carbide was prepared, and the composition by mass fraction was: 87.0%WC, 12%Co, 0.75%Cr3C2, 0.25%VC, wherein the powder particle size FSSS of WC was 0.4μm, and the powder particle size FSSS of Co was 1.0μm.

[0048] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0049] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 37.5 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic (density 6.5 g / cm 3 )D3 mm*L20 mm rod was used as the grinding body, the weight ratio of the grinding body to the powder material was 2:1, the rotation speed was 36 r / min, and after grinding for 24 hours, the pre-abrasive was dried and sieved to obtain the pre-abrasive.

[0050] (2) Weigh 600 g of pre-ground material and put it into a 1 L ball mill, then add 400 mL of hexane for grinding. Use D6 mm carbide balls as grinding bodies, the weight ratio of grinding body to powder material is 8:1, the rotation speed is 36 r / min, and after grinding for 6 hours, dry and sieve to obtain a mixed material.

[0051] (3) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0052] The metallographic and performance results of the sample alloy are shown in Table 1. The WC-12%Co ultrafine-grained cemented carbide prepared by the above two-stage grinding process has higher magnetic force and hardness and good coarseness control.

[0053] Comparative Example 1

[0054] WC-6.5%Co ultrafine-grained cemented carbide is prepared, and the composition is: 92.6%WC, 6.5%Co, 0.55%Cr3C2, 0.35%VC by mass fraction. The powder particle size FSSS of WC is 0.4μm, and the powder particle size FSSS of Co is 1.0μm.

[0055] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0056] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 37.5 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod was used as the grinding body. The weight ratio of the grinding body to the powder material was 2:1. The rotation speed was 36 r / min. After grinding for 24 hours, the mixture was dried and sieved to obtain a mixed material.

[0057] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0058] The main difference between Comparative Example 1 and Example 1 is that only Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod is used for grinding, and no subsequent cemented carbide ball grinding treatment is performed.

[0059] The results of the sample alloy are shown in Table 1. The magnetic force and hardness of the sample alloy are slightly lower than those of Example 1, and the magnetic force and hardness fluctuate greatly. Only the Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod is used for the grinding process, the grinding efficiency is low, the prepared mixed material powder particle size is large, and the alloy performance is relatively unstable.

[0060] Comparative Example 2

[0061] WC-6.5%Co ultrafine-grained cemented carbide is prepared, and the composition is: 92.6%WC, 6.5%Co, 0.55%Cr3C2, 0.35%VC by mass fraction. The powder particle size FSSS of WC is 0.4μm, and the powder particle size FSSS of Co is 1.0μm.

[0062] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0063] (1) 1.5 kg of raw material powder was put into a 3 L ball mill, and then 37.5 g of paraffin and 600 mL of hexane were added for grinding. D6 carbide balls were used as grinding bodies, the weight ratio of grinding body to powder was 8:1, the rotation speed was 36 r / min, and after grinding for 60 hours, the mixture was dried and sieved to obtain a mixture.

[0064] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0065] The main difference between Comparative Example 2 and Example 1 is that only D6 mm cemented carbide balls are used for grinding, and the grinding time is prolonged.

[0066] The results of the sample alloy are shown in Table 1. The magnetic force and hardness of the sample alloy are significantly lower than those of Example 1, and there is an obvious coarse inclusion phenomenon in the alloy. Using the above-mentioned traditional grinding process, even if the ball milling time is extended, the mixture cannot reach the ideal dispersion state, and the performance of the alloy is significantly reduced.

[0067] Comparative Example 3

[0068] WC-9%Co ultrafine-grained cemented carbide is prepared, and the composition is as follows: 89.9%WC, 9.0%Co, 0.85%Cr3C2, 0.25%VC by mass fraction, wherein the powder particle size FSSS of WC is 0.4μm, and the powder particle size FSSS of Co is 1.0μm.

[0069] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0070] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 45 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod was used as the grinding body. The weight ratio of the grinding body to the powder material was 2:1. The rotation speed was 36 r / min. After grinding for 24 hours, the mixture was dried and sieved to obtain a mixed material.

[0071] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0072] The results of the sample alloys are shown in Table 1. Compared with Example 2, the magnetic force and hardness of the sample alloys are slightly lower, and the alloy properties fluctuate greatly.

[0073] Comparative Example 4

[0074] WC-9%Co ultrafine-grained cemented carbide is prepared, and the composition is as follows: 89.9%WC, 9.0%Co, 0.85%Cr3C2, 0.25%VC by mass fraction, wherein the powder particle size FSSS of WC is 0.4μm, and the powder particle size FSSS of Co is 1.0μm.

[0075] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0076] (1) 1.5 kg of raw material powder was put into a 3 L ball mill, and then 45 g of paraffin and 600 mL of hexane were added for grinding. A D6 mm carbide ball was used as the grinding body, the weight ratio of the grinding body to the powder material was 8:1, the rotation speed was 36 r / min, and after grinding for 60 hours, the mixture was dried and sieved to obtain a mixture.

[0077] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0078] The results of the sample alloy are shown in Table 1. Compared with Example 2, the magnetic force and hardness of the sample alloy are significantly reduced, and the alloy has serious coarse inclusions.

[0079] Comparative Example 5

[0080] WC-12%Co ultrafine-grained cemented carbide was prepared, and the composition by mass fraction was: 87.0%WC, 12%Co, 0.75%Cr3C2, 0.25%VC, wherein the powder particle size FSSS of WC was 0.4μm, and the powder particle size FSSS of Co was 1.0μm.

[0081] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0082] (1) A total of 1.5 kg of raw material powder was put into a 3 L ball mill, and then 45 g of paraffin and 600 mL of hexane were added for grinding. Ti(C,N)-WC-Ni metal ceramic D3 mm*L20 mm rod was used as the grinding body. The weight ratio of the grinding body to the powder material was 2:1. The rotation speed was 36 r / min. After grinding for 24 hours, the mixture was dried and sieved to obtain a mixed material.

[0083] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0084] The results of the sample alloys are shown in Table 1. Compared with Example 3, the magnetism and hardness of the sample alloys are slightly lower, and the alloy properties fluctuate greatly.

[0085] Comparative Example 6

[0086] WC-12%Co ultrafine-grained cemented carbide was prepared, and the composition by mass fraction was: 87.0%WC, 12%Co, 0.75%Cr3C2, 0.25%VC, wherein the powder particle size FSSS of WC was 0.4μm, and the powder particle size FSSS of Co was 1.0μm.

[0087] Weigh a total of 1.5 kg of raw material powder (formulated material) according to the above mass fraction.

[0088] (1) 1.5 kg of raw material powder was put into a 3 L ball mill, and then 45 g of paraffin and 600 mL of hexane were added for grinding. A D6 mm carbide ball was used as the grinding body, the weight ratio of the grinding body to the powder material was 8:1, the rotation speed was 36 r / min, and after grinding for 60 hours, the mixture was dried and sieved to obtain a mixture.

[0089] (2) The mixed material is pressed into a cemented carbide blank, and then the blank is divided into three groups. A low-pressure sintering furnace is used to sinter the sample alloys at sintering temperatures of 1405°C, 1425°C and 1445°C, and the microstructure and properties of the sample alloys are tested.

[0090] The results of the sample alloy are shown in Table 1. Compared with Example 3, the magnetic force and hardness of the sample alloy are significantly reduced, and the alloy has serious coarse inclusions.

[0091] Table 1 Properties and microstructure results of the experimental alloys

[0092]

[0093]

[0094] Note 1: Evaluation method for inclusion coarseness: Mark 2-1-6-2 indicates: for the metallographic specimen, observe 10 fields of view at 1500 times magnification, and the total number of coarse grains of 1.5-3.0μm in the worst field of view is 2; observe 5 fields of view at 1500 times magnification, and the total number of coarse grains of 3.0-6.0μm in the worst field of view is 1; observe the entire grinding surface of the specimen at 200 times magnification, and the total number of coarse grains of 6.0-10.0μm is 6, and the total number of coarse grains ≥10μm is 2.

[0095] According to the comparison in Table 1, the magnetism, hardness and coarse inclusion of the sample alloys of Examples 1-3 are well controlled. The magnetism and hardness of the sample alloys of Comparative Examples 1, 3 and 5 are slightly lower than those of the corresponding Examples 1-3. The magnetism and hardness of the sample alloys of Comparative Examples 2, 4 and 6 are significantly lower than those of the corresponding Examples 1-3, and there are obvious coarse grains, and the coarse inclusion control is poor. The test data results show that the preparation process of an ultrafine-grained WC-Co cemented carbide mixture provided by the present invention can effectively avoid the abnormal growth of WC grains in the alloy, solve the problem of coarse inclusion, and effectively improve the performance of the alloy.

[0096] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing an ultrafine-grained cemented carbide mixture, characterized in that: The following steps are involved: (1) Weighing WC powder, Co powder, Cr3C2 powder and VC powder raw materials to obtain a formula material; (2) The formulated materials are ground and mixed in two stages, and a forming agent is added at the same time to obtain a mixed material, which is then pressed and sintered to obtain an ultrafine-grained WC-Co cemented carbide.

2. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 1, characterized in that: The formula material composed of WC powder, Co powder, Cr3C2 powder and VC powder in step (1) is composed of the following mass percentages: WC 86.9-92.7%, Co 6.5-12%, Cr3C2 0.5-0.9%, and VC 0.2-0.4%.

3. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 1 or 2, characterized in that: The molding agent is paraffin, and the dosage of the molding agent is 2.0-3.0% of the mass of the formula material.

4. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 1, characterized in that: The operation method of the two-stage grinding in step (2) is as follows: in the first stage of the grinding process, a lightweight Ti(C,N)-WC-Ni metal ceramic cylinder with a specification of D3-6mm×L10-20mm is used as the grinding body, and the weight ratio of the grinding body to the formula material is 2:1-4:1; The second grinding process uses D6-10mm carbide balls as grinding bodies, and the weight ratio of the grinding bodies to the formula materials is 4:1-8:

1.

5. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 4, characterized in that: The grinding media used in the first and second grinding stages are both hexane; Add 300-450 mL of grinding media per kg of formula.

6. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 4, characterized in that: The grinding speed of the first stage grinding is 36-40 r / min, and the grinding time is 12-36 h. The grinding speed of the second stage grinding is 36 r / min, and the grinding time is 6 to 18 hours.

7. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 4, characterized in that: The density of the lightweight Ti(C,N)-WC-Ni metal ceramic cylinder is 6.5 g / cm 3 .

8. The method for preparing an ultrafine-grained cemented carbide mixture according to claim 1, characterized in that: The sintering temperature in step (2) is 1405-1445° C., and the sintering holding time is 50-70 minutes.

Citation Information

Patent Citations

  • Ball milling method for preparation of hard alloy mixture

    CN102202817B

  • Preparation method for high-strength and high-hardness nanocrystalline tungstate-cobalt hard alloy

    CN102994792A

  • Preparation method of high bending strength nano wc-co alloy powder and wc-co alloy products

    CN103537702B

  • Method of making a cemented carbide or cerment powder by using a resonant acoustic mixer

    CN103890204A

  • A rare earth element-free ultrafine grain cemented carbide material and its preparation method

    CN109457163B